2022
DOI: 10.3389/fnut.2022.934113
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota–mitochondrial inter-talk in non-alcoholic fatty liver disease

Abstract: The increasing prevalence of non-alcoholic fatty liver disease (NAFLD), which is a progressive disease, has exerted huge a healthcare burden worldwide. New investigations have suggested that the gut microbiota closely participates in the progression of NAFLD through the gut–liver axis or gut–brain–liver axis. The composition of the microbiota can be altered by multiple factors, primarily dietary style, nutritional supplements, or exercise. Recent evidence has revealed that gut microbiota is involved in mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…Research indicates that alterations in the gut microbiota environment play crucial roles in the onset and progression of NAFLD. Both beneficial and detrimental gut metabolites are directly transported to the liver via the portal vein, contributing to a range of biological processes, encompassing energy production, detoxification, and synthesis [ 40 , 41 , 42 , 43 ]. In this study, we scrutinized the regulatory influence of Rg 5 intervention on the gastrointestinal flora of NAFLD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that alterations in the gut microbiota environment play crucial roles in the onset and progression of NAFLD. Both beneficial and detrimental gut metabolites are directly transported to the liver via the portal vein, contributing to a range of biological processes, encompassing energy production, detoxification, and synthesis [ 40 , 41 , 42 , 43 ]. In this study, we scrutinized the regulatory influence of Rg 5 intervention on the gastrointestinal flora of NAFLD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that there is a close link between the inflammatory response and the gut microbiota ( Jiang et al, 2020 ; Li et al, 2022 ; Zhang et al, 2022 ). Altered gut microbiota can mitigate or promote inflammatory processes ( Jiang et al, 2020 ; Pan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, high fat/high sugar diet, drugs, and microbiota products, such as fatty acids and bile acids, can concur to generate microbiota imbalance, altering the vagal–gut pathway and the liver’s glycolipid homeostasis, promoting gut inflammation, compromising intestinal permeability, and, therefore, contribute to NAFLD development. According to this pathogenetic model, a possible interaction between microbiota and mitochondria activity has been described since microbiota dysbiosis could dysregulate the mitochondria’s consumption of fatty acids and bile acids, the primary substrate for energy production and biogenesis [ 56 , 120 ]. Thus, this process may lead to mitochondrial dysfunction with consequent reactive oxygen species (ROS) accumulation and increased hepatic oxidative stress.…”
Section: Molecular Evidencementioning
confidence: 99%